Effects of cocaine on aggression and associated central ERα and oxytocin expression in ovariectomized and intact mandarin voles - Q. Q. Fang; J. L. Wang; F. D. Tai (The European Zoological Journal, 2017)
Ovarian hormones, especially estrogen, may facilitate drug use vulnerability in females. Oxytocin is of special relevance to females and an important neuroendocrine factor regulating drug use. Mandarin vole (Microtus mandarinus) is a monogamous rodent, with complex nonsexual social behavior. Here, we examined whether ovariectomy produces effects on cocaine-induced aggressive behaviors, estrogen receptor alpha (ERα) and oxytocin in virgin female mandarin voles. The data indicate that repeated cocaine exposure increased aggressive behavior and reduced levels of oxytocin expression in the paraventricular nucleus in ovariectomized and sham-operated females. In addition, cocaine reduced the levels of ERα expression in the medial nuclei of the amygdale in sham-operated females. In contrast, cocaine decreased ERα expression in the medial preoptic area and increased serum estradiol levels in ovariectomized females. These results suggest that ovariectomy influences the effects of cocaine on central levels of ERα and oxytocin expression and serum estrogen levels. The estrogen system acts in concert with oxytocin to regulate cocaine-induced aggressive behavior in virgin females.